Improve micro, small, and medium enterprises' competitiveness based on relational capital and innovative behaviour - Istikhoroh, Siti; Afkar, Taudlikhul; Ardhiani, Mutiara Rachma (Journal of Social Economics Research, 2024)
In Indonesia, the role of Micro, Small and Medium Enterprises (MSMEs) in improving the nation's economy cannot be doubted. This study seeks to examine the impact of innovative behaviour on enhancing competitiveness, the impact of relational capital on enhancing competitiveness, and the function of relational capital in amplifying the influence of innovative behaviour on strengthening competitiveness. The study was conducted on MSMEs Bags and Shoes in Tanggulangin Sidoarjo, Indonesia, in 2022. Data was taken by distributing questionnaires to 84 MSME Actors Bags and Suitcases Tanggulangin Sidoarjo, who are members of the. Cooperative and analyzed by Structural Equation Model _ Partial Least Square (SEM-PLS) analysis. The results of the analysis prove that innovative behavior has a direct effect on strengthening competitiveness, and relational capital has a direct effect on strengthening competitiveness but does not increase the magnitude of the influence of innovative behavior on strengthening competitiveness. Theoretically, the research results are useful for the development of strategic management science while being practically useful for MSME actors in managing their business activities. Therefore, high awareness is needed for MSME players to improve the quality of their services to customers in order to build better relational relationships while not ignoring the importance of innovation.